2021
DOI: 10.1523/jneurosci.1479-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Reduction of Mitochondria Complex I Subunits is Protective against Cisplatin-Induced Neurotoxicity inDrosophila

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a prevalent side effect of widely used platinum-based anticancer agents. There are few predictable risk factors with which to identify susceptible patients. Effective preventive measures or treatments are not available. Here, we have used a model of CIPN in Drosophila melanogaster to identify genetic changes that confer resistance to cisplatin-induced neuronal damage but not in the rapidly dividing cells of the ovary. The Drosophila strain attP40, used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…2022). In addition, this study also reported defects in muscle nuclei spacing in larval stages in the attP40 homozygous background, which phenocopies Msp300 mutants ( van der G raaf et al . 2022).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…2022). In addition, this study also reported defects in muscle nuclei spacing in larval stages in the attP40 homozygous background, which phenocopies Msp300 mutants ( van der G raaf et al . 2022).…”
Section: Introductionsupporting
confidence: 57%
“…Thus, use of full animal mutants or MARCM based clonal mutant analysis should be coupled with RNAi-based phenotypic analyses. Though the underlying genetic reasons remain elusive, studies demonstrated that the attP40 landing site on chromosome II affects the expression of multiple genes (GROEN et al 2022; VAN DER GRAAF et al 2022). Additional omics-based experiments in the future will be needed to determine all the genetic lesions in the attP40 strain that underly many phenotypic defects observed in this background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we used UAS-RNAi lines as a screening tool. A recent study demonstrated that RNAi lines with an attP40 insertion site may have a reduction in adjacent ND-13A expression, and ND-13A encodes an MCI accessory subunit ( Groen et al, 2022 ). For our work, this could mean that any attP40 lines are sensitized to MCI impairment and potentially lower neurotransmission.…”
Section: Discussionmentioning
confidence: 99%